Pengaruh Campuran Minyak Jarak Pagar dengan Dexlite Terhadap Performa Mesin Diesel - Andinusa Rahmandhika; Nur Hasanah; Rizqi Arif Viandi; Achmad Fauzan Hery Soegiharto (Universitas Muhammadiyah Yogyakarta, 2024)
One of the alternative energy fuels in the transportation sector is biodiesel. Biodiesel made from a mixture of vegetable materials has great potential as an environmentally friendly fuel for diesel engines. This experimental research aims to analyze the effect of using Jatropha curcas (Jatropha curcas Linn) oil on diesel engines. The experiment was carried out using a mixture of Dexlite and pure castor oil (JCO) with varying compositions of JCO 0%, JCO 20%, and JCO 30%. Torque test results against load show an insignificant comparison between Dexlite without mixture and Dexlite with 20% and 30% JCO mixture, especially when loading high using Prony Brake. Although the effective engine power of the three fuel variations does not show significant differences at the same engine speed and load, the use of a mixture of Dexlite and 20% castor oil at an engine speed of 1700 rpm is more effective in improving diesel engine performance and saving fuel. Additionally, fuel consumption decreases as load increases, indicating high efficiency potential. In the context of exhaust gases, the mixture also has the potential to reduce the opacity of diesel engine exhaust gases.